Mesoporous silica nanoparticle-templated ionic liquid as a drug carrier for ibuprofen and quercetin - Najihah Rameli,; Khairulazhar Jumbri,; Anita Ramli,; Roswanira Abdul Wahab,; Haslina Ahmad,; Mohd Basyaruddin Abdul Rahman, (Penerbit Universiti Kebangsaan Malaysia, 2022)
In this study, a series of mesoporous silica nanoparticle (MSN) was successfully synthesized using different ionic liquids (ILs) as a template. Five ILs and a surfactant with different alkyl side chains and types of anion namely 1-dodecyl-3-methylimidazolium iodide ([C12mim][I]), 3-diethylamino propanol vanillate (DV), 2-butylamino ethanol salicylate (BS), 3-diethylamino propanol salicylate (DS), 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl) imide ([bmim][NTf 2 ]) and hexadecyltrimethylammonium bromide (CTAB) were used. All MSNs produced have broad peaks, indicating mesoporous silica in amorphous form as observed by XRD while the morphology of MSN showed the agglomeration of particles and due to parallel arrangement pores size in both for FESEM and HRTEM. The MSNs are amorphous and displayed Type IV BET isotherm with H2 hysteresis loops which is a typical isotherm for mesoporous materials and the highest surface area obtained was 638 m2 /g. The study on uptake and release of ibuprofen and quercetin were carried out, where ibuprofen showed higher drug uptake compared to quercetin due to better interaction of MSN with drug molecules. The drug release conducted at 48 h indicates 33.1% of ibuprofen and 38.4% quercetin released. It can be indicated that MSN-BS is the best for drug loading and release. Drugs release kinetics study indicated that the release process follows the Korsmeyer peppes model. The best efficiency of drug loading for MSN-BS/IBU and MSN-BS/QUE was at 48 h and 25 °C with 250 rpm stirring rate for both IBU and QUE, respectively.